Virtual reality : the last human narrative?. - Botz-Bornstein, Thorsten. (Critical Posthumanisms, 2015)
Is virtual reality the latest grand narrative that humanity has produced? Our civilization is determined by a shift from an "original event" to a virtual "narrative". This concerns not only virtual reality but also psychoanalysis, gene-technology, and globalization. Psychoanalysis transforms the dream into a narrative and is able to spell out the dream's symbols. Gene-technology narrates dynamic, self-evolving evolution as a "gene code". Discourses on "globalization" let the globe appear as once more globalized because reproduced through narrative. Finally, reality itself has come to be narrated in the form of a second reality that is called "virtual". This book attempts to disentangle the characteristics of human reality and posthuman virtual reality and asks whether it is possible to reconcile both.